Effect of Myristic Acid Supplementation and Calliandra (Calliandra calothyrsus) on Complete Feed-based Corn Straw on Crude Protein Digestibility and Ammonia In Vitro - Maharani, Auliya Sartika; Chuzaemi, Siti; Mashudi, Mashudi (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
ABSTRACTThe research purposed to evaluate the effect of Myristic acid supplementation and condensed tannins sourced from calliandra leaf flour on a complete feed-based corn straw on Crude Protein Digestibility (CPD) and ammonia (NH3). The research was conducted in vitro. The treatment used was: P1 = Complete Feed (40% corn straw + 60% concentrate), P2 = Complete feed (40% corn straw + 60% concentrate + 0% calliandra leaf flour + myristic acid 30 g/kg DM, P3 = Complete feed (40% corn straw + 35% concentrate + 25% calliandra leaf flour + myristic acid 30 g/kg DM, P4 = Complete feed (40% corn straw + 30% concentrate + 30% calliandra leaf flour + myristic acid 30 g/kg DM,  P5 = complete feed (40% corn straw + 25% concentrate + 35% calliandra leaf flour + myristic acid 30 g/kg DM. The variables of research were the nutritional content of DM, OM, CP, CF, EE, Ash, NDF, ADF, CPD, and NH3. The data obtained were analyzed using the Randomized Block Design (RBD) method consisting of 5 treatments and 3 repeats. If data shows a significant difference, proceed with Duncan Multiple Range Test (DMRT). The results showed a very significant difference in CPD increase and un significant difference in NH3 increase. The increase of NH3 was still normal amounts for rumen microbes’ growth. The conclusion of this research was the best treatment for P5 (complete feed 40% corn straw + 25% concentrate + 35% calliandra leaf flour + Myristic acid 30 g/kg DM), P5 could increase rumen fermentation products in vitro.Keywords: calliandra, myristic acid, in vitro, rumen fermentation products